P 96 Patients' beliefs and resuscitation statistics – Mere coincidence or a causal link?. Issue 10 (October 2017) - Spiegel, R.; Sutter, R.
Abstract : Introduction: Imagine being a physician in the Emergency Department (ED) on Christmas. Suddenly, one of your patients approaches you and tells you that the conincidence of full moon and Christmas will cause unusual things. Having received a rational education in university, you of course do not take this patient seriously. Suddenly, however, you experience more resuscitations of initially stable patients than expected from available statistics. The success rate of these resuscitations also turns out higher than expected. Objective: In 2015, a full moon dawned on Christmas. We aimed to analyze whether this rare event was associated with an increase of cardiac arrests in the Emergency Department (ED) as compared to the number of events on other Christmas and non-Christmas days and further to assess respective outcomes of resuscitation. Design: Retrospective, cohort study. Setting: The ED of a Swiss academic tertiary medical care centre. Participants: All patients admitted to the emergency department excluding minor injuries (which were treated in a separate unit) during the full moon on Christmas eve and Christmas day 2015 were compared to control cases on other Christmas and non-Christmas days. For comparisons regarding successful resuscitation, published data as collected by the American Heart Association during 2015 served as a reference. Main outcome measure: Number of resuscitations per total number of admissions and proportion of successful resuscitations. Results: On Christmas 2015, three out of 24 patients (12.5%) required in-hospital resuscitation, whereas none of the 95 control-patients had to be resuscitated (Odds ratio = 31.1, 95% CI = 1.55–624.5, p  = 0.02). All three resuscitations were successful, which differed significantly from success rates of in-hospital resuscitation statistics for the year 2015, Odds ratio 20.4, 95% CI = 1.06–395.9, p  = 0.046 (American Heart Association, 2015 ). Conclusions: The coincidence of full moon and Christmas was associated with significantly more cardiac arrests in the emergency department than on other days and resuscitations were significantly more successful than expected. How can these seemingly bizarre findings be explained? It seems unreasonable that patients" beliefs can have effects this strong. On the other hand, evidence-based medicine cannot be applied because the coincidence of full moon and Christmas (in the years 1977, 2015) only happens every couple of decades and has not been studied before. Full moon alone does not seem to have an effect on resuscitations (Alves et al., 2003 ). whereas Christmas is related to a higher number of deaths (Phillips et al., 2004 ). The retrospective nature limits the validity of our results and calls for prospective, multicentre trials in 2034, when the next full moon is expected to dawn on Christmas.